Lignite-Derived Activated Carbon: A Superior, Low-Cost Alternative to Coconut-Shell GAC for Tributyl Phosphate (TBP) Adsorption from Wastewater - Guk Chol Kim; Jong Hyok Kim; Yong A. Choe; Jin Song O (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
This study examined the use of local lignite-based and walnut shell-based GACs as potential low-cost alternatives to the imported coconut shell-based GACs for the removal of TBP from wastewaters in Zr alloy production. The lignite-based GAC steam activated showed that the surface groups consisted of –OH, C=C, and C–O–C and that it had a predominantly mesoporous structure (65% mesopores and 20% micropores). At a solid-to-liquid ratio of 1:100 and an initial concentration of 400 mg/L of TBP, the GAC derived from lignite adsorbed 38.7 mg/g with an efficiency of 96.2%. This result was comparable to the coconut shell GAC, which adsorbed 39.8 mg/g with an efficiency of 99.5%. The walnut shell GAC had a slightly higher adsorption capacity than the other two GACs, with 39.7 mg/g and an efficiency of 99.6%. In all cases, equilibrium was reached in 120 min, while the literature usually reports 150–180 min. This may be because the intraparticle diffusion is accelerated when the mesopore content is high; in this GAC, the mesopores accounted for 65% of the volume. This kinetic advantage distinguishes domestically produced GACs from predominantly microporous coconut-shell GAC. Economically, lignite-derived GAC showed superior cost-effectiveness, with a production cost less than one-fifth that of imported coconut-shell GAC. The economic effectiveness index clearly favoured domestically produced GACs. Lignite-derived GAC, originally used almost exclusively for gas purification, was successfully validated for liquid-phase TBP removal, an application with no prior example. Thus, domestically produced lignite-derived GAC is an effective, low-cost alternative to imported coconut-shell GAC for TBP removal from Zr alloy production wastewater. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).